Posttraumatic growth in family members of individuals with methamphetamine use disorder - Turan, Çetin; Ünal, Süheyla; Şenormancı, Güliz; Şenormancı, Ömer (The European Research Journal, 2023)
Objectives: This study aimed to determine post-traumatic growth and its predictors in female relatives of patients with methamphetamine use disorder. Methods: The volunteers in our study consisted of 80 adult women who were first-degree relatives of male patients diagnosed with MUD. The Post-Traumatic Growth Inventory, the Hospital Anxiety-Depression Scale, the Impact of Events Scale , and the short form of the Coping with Stressful Situations Inventory were given to the relatives of the patients. Results: In our study, being employed and being married were found to affect task-oriented coping and changes in self-perception positively. Task-oriented coping or seeking emotional support from others predicted higher PTG. Task-oriented coping was positively associated with emotional coping and a change in the philosophy of life. The regression analysis determined that task-oriented and avoidant coping mechanisms were the best predictors of post-traumatic growth. Conclusions: The findings suggest that environmental and personal factors, such as being married, being employed, and the quality of social relationships that emerge with emotional and instrumental support, influence the experience of life crises. In addition, the duration of methamphetamine uses, the problem's, and the search for solutions were all associated with higher post-traumatic growth. Thus, the results of this study demonstrate that task-oriented coping, seeking emotional support, and the duration of methamphetamine use may contribute to post-traumatic growth.